Jazzing : New York City's Unseen Scene - Greenland, Thomas H., 1961- (Book collections on Project MUSE., 2016)
"How do we speak about jazz? In this provocative study based on the author's deep immersion in the New York City jazz scene, Tom Greenland turns from the usual emphasis on artists and their music to focus on non-performing participants, describing them as active performers in their own right who witness and thus collaborate in a happening made one-of-a-kind by improvisation, mood, and moment. Jazzing shines a spotlight on the constituency of proprietors, booking agents, photographers, critics, publicists, painters, amateur musicians, fans, friends, and tourists that makes up New York City's contemporary jazz scene. Drawn from deep ethnographic research, interviews, and long term participant observation, Jazzing charts the ways New York's distinctive physical and social-cultural environment affects and is affected by jazz. Throughout, Greenland offers a passionate argument in favor of a radically inclusive conception of music-making, one in which individuals collectively improvise across social contexts to co-create community and musical meaning. An odyssey through the clubs and other performance spaces on and off the beaten track, Jazzing is an insider's view of a vibrant urban art world."--Publisher description